Surgical Management of Hirschsprung's Disease: A Comparative Study Between Conventional Laparoscopic Surgery, Transumbilical Single-Site Laparoscopic Surgery, and Robotic Surgery - Li, Wei; Lin, Minghui; Hu, Hai; Sun, Quanfeng; Su, Cheng; Wang, Congjun; Li, Yanqiang; Li, Yong; Chen, Jiabo; Luo, Yige (Frontiers in Surgery, 2022)
Background: Hirschsprung's disease (HD) is a commonly digestive malformation in children that usually requires surgery. This study aims to evaluate the short-term efficacy of conventional laparoscopic surgery (CLS), transumbilical single-hole laparoscopic surgery (TU-LESS), and robotic surgery (RS) in the treatment of Hirschsprung's disease. Methods: 90 patients with Hirschsprung's disease undergone laparoscopic surgery at our center between 2015 and 2019, divided into three groups (group CLS, TU-LESS and RS), were retrospectively analysed. Results: CLS and TU-LESS group showed no significant difference in operation duration (P >0.05) but shorter operation duration than the RS group (P <0.05). RS group had highest overall SCAR scores, while TU-LESS group had the lowest one (P <0.05). Other parameters such as operative blood loss, hospital stays, recovery time of digestive function, postoperative complications had no significant difference among the three groups (P >0.05). Conclusion: The three surgical methods for HD revealed similar efficacy, where TU-LESS and CLS spent less time than RS; TU-LESS led to the most aesthetic effect, followed by CLS and RS.